Analiza grešaka u pismenim radovima (Philologia, 2021)
This paper deals with cross-sectional error analysis of written papers (essays) of 3rd year students at the Department of English in order to determine the level of acquisition of grammatical structures which were practised throughout the school year. The main idea has been to test whether Krashen’s hypotheses (language-acquisition hypothesis and natural order hypothesis) are applicable to students whose mother tongue is Serbian. The paper emphasizes the importance of acquisition and tries to give a starting point for future work with students.